Bohmian trajectory-bloch wave approach to dynamical simulation of electron diffraction in crystal. (6th November 2018) - Cheng, L; Ming, Y; Ding, Z J
Abstract: The Bohmian trajectory method is employed to study electron diffraction in crystalline materials. It provides a fresh understanding of the process of electron diffraction, including traveling channels of electrons and formation of diffraction patterns. By combining it with the Bloch wave method, the electron trajectories can be calculated more efficiently than the traditional wave-packet propagation algorithm. Meanwhile, we propose a momentum expectation approach which is a good approximation method with even higher computational efficiency. Both methods result in intuitive and accurate electron trajectories for the simulation of the electron backscatter diffraction (EBSD) pattern. Excellent agreement has been obtained between the simulated trajectory distributions and the experimental EBSD pattern from Mo (001) at 20 kV, where the Kikuchi patterns and higher order Laue zone rings are characterized.